2014
DOI: 10.1111/jog.12547
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of induced abortion among rural married women: A cross‐sectional survey in Anhui, China

Abstract: The study shows that the prevalence of induced abortion is still very high among married women in rural China, and highly effective methods of contraception (sterilization, intrauterine device) decrease women's recourse to induced abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
7
14
4
Order By: Relevance
“…Another study from India reported a 3.8% prevalence of abortion [ 22 ], which is reportedly lower than ours. Similarly, another study from China has reported a 22.0% prevalence of abortion [ 17 ] , which is more or less similar to that of our study populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another study from India reported a 3.8% prevalence of abortion [ 22 ], which is reportedly lower than ours. Similarly, another study from China has reported a 22.0% prevalence of abortion [ 17 ] , which is more or less similar to that of our study populations.…”
Section: Discussionsupporting
confidence: 91%
“…Especially young, economically deprived and those without a supportive male partner are at higher risk of unsafe abortion [ 16 ]. An earlier study reported that rich and well-educated women are more likely to have an abortion than are poor and illiterate women [ 17 ]. However, there is no clear and established evidence on this issue, especially in low- and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirmed that women with lower education levels had a high risk of induced abortion [ 23 ]. However, Guo et al conducted a reproductive health survey with 4,687 persons regarding floating population in five cities in China in 2005.…”
Section: Discussionsupporting
confidence: 86%
“…In such cases, the study population may not be representative of all women obtaining abortions. Other studies have investigated the characteristics of women who report ever having an abortion, including women who had abortions long before the time of the survey [6, 14, 15]. These findings can be misleading if a woman is classified according to her characteristics at the time of the survey, and these characteristics differ from those at the time of her abortion.…”
Section: Introductionmentioning
confidence: 99%